2014
DOI: 10.1603/en13267
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory Behavior and Fungal Infection ofAnoplophora glabripennis(Coleoptera: Cerambycidae)

Abstract: Asian longhorned beetles, Anoplophora glabripennis (Motschulsky), are invasive wood borers that are native to China and Korea but have been introduced to North America and Europe. These beetles have great potential to negatively impact economic and environmental interests in hardwood and urban forests if they become established. The entomopathogenic fungus Metarhizium brunneum Petch (previously Metarhizium anisopliae (Metschnikoff) Sorokin) is under development for control of A. glabripennis. Some insect speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Some insects seek lower temperature environments that presumably slow down fungal development, giving the insect more time to mount an effective defense response to resist the pathogen (Hunt et al ., ). Quite a few insects do not regulate temperature but their survival is vastly improved if kept at higher temperatures, as reported for the Asian longhorned beetle, Anoplophora glabripennis (Motschulsky) exposed to Metarhizium brunneum (Fisher & Hajek, ).…”
Section: Introductionmentioning
confidence: 91%
“…Some insects seek lower temperature environments that presumably slow down fungal development, giving the insect more time to mount an effective defense response to resist the pathogen (Hunt et al ., ). Quite a few insects do not regulate temperature but their survival is vastly improved if kept at higher temperatures, as reported for the Asian longhorned beetle, Anoplophora glabripennis (Motschulsky) exposed to Metarhizium brunneum (Fisher & Hajek, ).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, it appeared that mature and old females of A. glabripennis were more susceptible to M. brunneum than males of equal ages, and more females had detectable fungal blastospores in their hemolymph compared to mature and old males [135]. Also, laboratory conditions demonstrated that M. brunneum -infected A. glabripennis does not exhibit behavioral fever (elevating body temperature by exposing to a heat source to ward off fungal infections [136]. Bioassays conducted in the United States showed that the Japanese commercial strain of B. asiatica and the commercial strain F52 of M. brunneum were more virulent than two North American B. brongniartii isolates against A. glabripennis [137].…”
Section: Microbial Control Of Invasive Pests With Entomopathogenicmentioning
confidence: 99%
“…For example, the choice of luminant (i.e. bulb versus LED) can make a considerable difference in heat development during the experiment, which can become problematic if not compensated, since some fungi such as Metarhizium brunneum are considerably temperature sensitive [ 36 ]. Unwanted light impulses even in the range of seconds (e.g., by opening the lid of an incubator system within a room without controlled light conditions) can already alter fungal metabolism [ 25 , 30 , 37 ] and thus distort the observed photo response.…”
Section: Introductionmentioning
confidence: 99%